The Euro: The issues for the future - Horst Siebert (Institut für Weltwirtschaft (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2000)
The euro is a new currency, and the ECB as a new institution still has to establish its reputation. The best way to do this is for the ECB to deliver a stable money. The two-pillar strategy pursued by the ECB seems to confuse the markets because market participants are unclear about which of the two pillars is the dominating one. The ECB will have to rethink its strategy and move more in the direction of the monetary targeting approach. A central bank cannot have two nominal anchors for its currency, both the internal price level and the external value of a currency. Admittedly, a low external value may translate into inflationary expectations or expectations on further depreciations. These effects cannot be neglected by the ECB. Therefore, it has to factor in the impact of depreciation on the future price level. Member countries of the common currency area may free ride on the common currency. Although a Minhas Gerais problem in the European Monetary Union is unlikely, countries with high indebtedness may put pressure on the ECB to follow a rather lax monetary policy characterized by low interest rates and a (slightly) higher inflation rate than the one anticipated by financial markets. The stability pact has to shield the ECB against such pressures. National economic policies in the three major continental countries, Germany, France, and Italy, have severe difficulties in establishing the necessary institutional conditions in the national labor markets for a smooth functioning of the common currency. Interest groups in the member countries will defend their political position and will resist necessary institutional changes. Wage policy should be decentralized and not europeanized. Employment policy should not be europeanized either. In attracting new members, care must be taken not to increase the heterogeneity of the monetary union. This relates to the candidates for new EU membership; they will need the exchange rate for quite some time. For the UK, only a short time window in which the business cycle in the UK and that in EMU are in a similar phase will allow entry. Two types of conflict have to be distinguished: "Type-1 conflict" is a conflict between the monetary authority and politics on the weight that should be assigned to a stable money or to other targets. "Type-2 conflict" is a conflict between national political decision-making and the europeanized monetary policy in the case of a major national economic crisis. The worst case that can be envisioned for the new monetary arrangement is a fundamentally divergent economic situation in a major country while at the same time the other economies in the rest of euroland are doing fine. An ingredient of such a scenario would be a major national crisis, for instance a homemade crisis due to severe policy failure. Such a major crisis will be the real test for the euro. Politics has to accept the depolitization and the denationalization of the common monetary policy. Relying on goodwill may not be sufficient to solve potential conflicts. Mechanisms have to be developed that make sure that goodwill is not the only basis for withstanding a major crisis. One way is to change the democratic set-up of political decision-making by giving more weight to European aspects. This raises severe questions which relate to the political concept for Europe and its federal structure, to the issue of a European constitution, and to the very basic question whether a European sovereign — a European people — is beginning to exist. Another approach is to create a European audience for the ECB's policy as well as for economic policy issues in general. Establishing a European Council of Economic Advisers is a step in this direction.
Keywords: 330; Euro; Prestige; Europäische Wirtschafts- und Währungsunion; Geldpolitik; Public Choice; EU-Staaten